Efektivitas Lubang Resapan Organopori Dalam Menahan Laju Erosi Dan Stabilitas Ekologi Tanah Pada Aliran Das Citarum, Dusun Tujuh, Desa Mulyasejati, Kabupaten Karawang, Jawa Barat - Rahmayanti, Fetty Dwi; Diana, Tungga Buana; Husni, Husni (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2020)
Tujuh Village is geographically intersected with Citarum watersheds and according to the Regional Government of West Java Province (2019); this village is one of the areas prioritized by the government to become a land and water conservation area in the national program of "Citarum Harum". Tujuh Village has the characteristics of an uneven and hilly region with relatively dry mineral soil and limited water availability that will experience drought in a number of places during dry season. The objectives of this community service program are (1) providing knowledge to farmers regarding soil and water conservation techniques using Organopore Infiltration Hole and (2) controlling organic waste from agricultural activities. One of the solutions to overcome the environmental and biophysical problems that occur in Tujuh Village is by making an Organopore Infiltration Hole. The principle of this organopore hole is almost the same as the Biopore Infiltration Hole, which is making a vertical hole with a diameter of 10 cm and a depth of 0-100 cm. The difference is that this organopore hole uses a basket made of wire to collect organic waste that will be made into natural compost within the hole that can improve soil ecological stability. The research was implemented by adopting the Participatory Rural Appraisal (PRA) approach, which allows sub-district communities to share, improve and analyze their knowledge regarding village conditions and life, as well as plan and perform concrete actions.